Advantages and recent advances of smart energy grid - Mohammed Qasim Taha (Institute of Advanced Engineering and Science, 2020)
Smart grid is widely recognized technology used to improve the stability and losses of the electric power system. It is encouraging reliability, efficiency, and effective control of the supply of electrical energy. However, it is a hot topic for recent publications and still has a limited understanding among researchers. This review work is to provide insight and support to the beginner researchers since this topic needs a multidisciplinary background knowledge. The conventional electric transmission system and distribution networks struggle to provide resilient performance and reliable service and real-time data. Also, smart grid id a promising network maneuver to stabilize the system once any disturbances break out by using the distributed renewable energy generators, while the conventional networks lack for flexibility to integrate with renewable energy generators or microgrids. This comprehensive work is conducted to map previous controbution in a coherent manar, including the specifications, features, and fundamentals that are presented to benefit the interested readers interested in smart grid development.